Crisis communication in China : strategies taken by the Chinese government and online public opinion - Cui, Wei (Digital activism and society., 2022)
While past public crises were addressed by focusing on protecting the public safety and maintaining public order, public crises today, such as the COVID-19 outbreak, require different responses and face more challenges. Crisis Communication in China examines crisis communication strategies taken by the Chinese government during public crises and discusses how the public react to these strategies, exploring the cultural context and the development of digital media as critical factors underlying the strategies adopted. Much of the previous research on crisis communication in China adopted Coombs' Situational Crisis Communication Theory. However, as a theory proposed and developed in the West, its application in a non-Western culture requires testing. In addition, cultural influences and the role of digital technology have been discussed in some existing literature, but few studies have attempted to integrate these elements into crisis communication theories. In order to fill these two gaps, this research analyses the Chinese government's crisis communication strategies during the H7N9 crisis, examining not only the government's management of the crisis but also the public's reaction to the official communication process. It also explores the cultural context and the development of digital media as critical factors underlying the strategies adopted. The analysis contributes to development of a comprehensive theory that incorporates these two elements, which shows and identifies related crisis communication strategies emerged from cultural traditions and the development of digital media.